A type-II NGyne/GaSe heterostructure with high carrier mobility and tunable electronic properties for photovoltaic application. (5th February 2023) - Zeng, Liru; Zhang, Siyu; Yao, Linwei; Bi, Zhisong; Zhang, Yanni; Kang, Peng; Yan, Junfeng; Zhang, Zhiyong; Yun, Jiangni
Abstract: The two-dimensional heterostructures with type-II band alignment and super-high carrier mobility offer an updated perspective for photovoltaic devices. Here, based on the first-principles calculation, a novel vertical NGyne/GaSe heterostructure with an intrinsic type-II band alignment, super-high carrier mobility (10 4 cm 2 V −1 s −1 ), and strong visible to ultraviolet light absorption (10 4 –10 5 cm −1 ) is constructed. We investigate the electronic structure and the interfacial properties of the NGyne/GaSe heterostructure under electric field and strain. The band offsets and band gap of the NGyne/GaSe heterostructure can be regulated under applied vertical electric field and strain efficiently. Further study reveals that the photoelectric conversion efficiency of the NGyne/GaSe heterostructure is vastly improved under a negative electric field and reaches up to 25.09%. Meanwhile, near-free electron states are induced under a large applied electric field, leading to the NGyne/GaSe heterostructure transform from semiconductors to metal. Our results indicate that the NGyne/GaSe heterostructure will have extremely potential in optoelectronic devices, especially solar cells.